Identification of a locus controlling expression of luminescence genes in Vibrio harveyi. - Martin, M (1989)
Mutagenesis with transposon mini-Mulac was used to identify loci containing genes for bioluminescence (lux) in the marine bacterium Vibrio harveyi. Transposon insertions which resulted in a Lux- phenotype were mapped to two unlinked regions of the genome. Region I contained the luxCDABE operon which was previously shown to encode the enzymes luciferase and fatty acid reductase, which are required for light production. The other locus, region II, which was identified for the first time in this study, appeared to have a regulatory function. In Northern blot analysis of mRNA from mutants with defects in this region, no transcription from the luxCDABE operon could be detected. Strains with transposon-generated lux::lacZ gene fusions were used to analyze control of the transcription of these regions. Expression of luminescence in the wild type was strongly influenced by the density of the culture, and in strains with the lacZ indicator gene coupled to the luxCDABE operon, beta-galactosidase synthesis was density dependent. So, transcription of this operon is responsive to a density-sensing mechanism. However, beta-galactosidase synthesis in strains with lacZ fused to the region II transcriptional unit did not respond to cell density. The organization and regulation of the lux genes of V. harveyi are discussed, particularly with regard to the contrasts observed with the lux system of the fish light-organ symbiont Vibrio fischeri.